2007
DOI: 10.1007/s10803-007-0358-4
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Adults with Mild Autism Spectrum Disorders (ASD): Scores on the Autism Spectrum Quotient (AQ) and Comorbid Psychopathology

Abstract: While knowledge about symptom presentation of adults with mild ASD, including comorbid psychopathology, is limited, referral of adults with suspected mild PDD is increasing. We report on pilot research investigating whether patients diagnosed with mild ASD (n = 15) and patients who were not diagnosed with ASD (n = 21) differed in terms of (a) AQ scores and (b) Axis I and II disorders, assessed by the SCAN and the IPDE. Additionally, AQ scores were compared with those from non-ASD patients referred to a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 13 publications
6
57
2
Order By: Relevance
“…However, no additional formal diagnosis was obtained. Moreover, the participants' scores on the Autism-Spectrum Quotientwhile significantly higher than those of our TD participants-were not firmly within the range associated with ASD, particularly in Experiment 1 (but see Ketelaars et al 2008). A more conservative interpretation of our results would therefore be that people with higher scores on the Autism-Spectrum Quotient show a profile of dialect perception that is consistent with the general profile of ASD.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, no additional formal diagnosis was obtained. Moreover, the participants' scores on the Autism-Spectrum Quotientwhile significantly higher than those of our TD participants-were not firmly within the range associated with ASD, particularly in Experiment 1 (but see Ketelaars et al 2008). A more conservative interpretation of our results would therefore be that people with higher scores on the Autism-Spectrum Quotient show a profile of dialect perception that is consistent with the general profile of ASD.…”
Section: Discussioncontrasting
confidence: 69%
“…As a group, the adults with HFA in the current study did not earn a mean score above this critical point and only 7 of the 23 participants with HFA scored above 32. However, other research has similarly found that people with positive ASD diagnoses do not always obtain such high scores on the Autism-Spectrum Quotient, and the scores of the participants in the current study were comparable to scores found in other HFA populations (Ketelaars et al 2008;Woodbury-Smith et al 2005). Moreover, the participants with HFA in the current study were recruited from a program specifically designed to help people with HFA improve their communicative abilities and social skills, which are among the specific elements targeted by the Autism-Spectrum Quotient.…”
Section: Autism-spectrum Quotientsupporting
confidence: 70%
“…These findings provide further evidence of a lack of differentiation between implicit and explicit mentalizing processes as well as a lack of correspondence between subjective self-reported mentalizing abilities and objectively measured mentalizing in individuals with ASD, which is possibly due to a lack of introspection into their social-cognitive deficits. For instance, self-reported symptom severity does not adequately differentiate autistic patients form other patient groups (Ketelaars et al 2008) and does not correlate with scores on a standard diagnostic instrument, such as the ADI-R (Bishop and Seltzer 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, symptoms of ASD are frequently present in children and adults with mood and anxiety disorders, especially Social Anxiety Disorder (SAD; Cath et al 2008;Pine et al 2008). Individuals who have ASD, including those with sub-clinical ASD features, are more likely than peers without ASD to be diagnosed with multiple mood and anxiety disorders (e.g., Kunihira et al 2006;Ketelaars et al 2008;Rosbrook and Whittingham 2010). Empirical studies of anxiety in children and adolescents with ASD reveal a wide range of comorbidity estimates (i.e., 11-84%), although the majority of studies report problematic anxiety among 40-45% of children with ASD ).…”
Section: Introductionmentioning
confidence: 99%